E-Real Estate Management System / Sandeep Singh Mukhtiar Singh - Sandeep Singh, Mukhtiar Singh (2004)
Real estate property is a growing marker which as a lot of future and hope in Malaysia. Whether real estate property is for investment of for personal use, its storng command in the markert is undeniable. It is soon becoming a very attractice business to people who have interset in it . With the the astonishing bing growth of the Internet, real estate companies are beginning to find new ways to expand their business as Internet and E-commerce has given businesses the ability to interact closely with end consumers. They want to add value to their services and thus an online system would help them achieve that target. Online real estate is expected to meet the ever increasing demands for the new properties. E - Real Estate Management System is a an automated system for property-related service on the Internet. This project is aimed at developing a web based online real estate application. With this system, real estate agents, potential buyer, seller , landlords, and other parties in real estate dealings can easily collaborate in a secure Web environment. This automation uses the internet to increase buyers' utility through information accessibility and efficiency in real estate dealings cornpared to the traditional business approach. The main features of this web site would be to post and view property listings; search for commercial, industrial, and residential property ; calculate loan amount; to gain total information on real estate and get profesional help and advice on it: financing solutions; and feng shui advice on property. Features mentioned above are expected to spe d up the buying and selling proces ; provide an easier, convenient and faster mode for finding relevant detail about commercial, Industrial, and residential properties fot rent or for sale; promote online property advertising and listings; and provide the user with unsurpassed servic and content when it comes to shopping for property online. Gone are those days of waiting and doing things manually. This project aims to make the best use of online technology to help the buying and selling processes. Automated features provided will further enhance the systems functionality and thus giving users a much wanted all round system for real estate propertu buying and selling.